2019
DOI: 10.1109/jphotov.2019.2941770
|View full text |Cite
|
Sign up to set email alerts
|

Development of Germanium-Based Wafer-Bonded Four-Junction Solar Cells

Abstract: Multijunction solar cells with four junctions are expected to be the next-generation technology for both space and concentrator photovoltaic applications. Most commercial triplejunction solar cells are today grown on germanium, which also forms the bottom subcell. Extending this concept to four junctions with an additional ∼1-eV subcell was proven to be challenging. We investigate a new cell concept, which uses direct wafer bonding to combine a metamorphic GaInAs/Ge bottom tandem solar cell with a GaInP/AlGaAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Presently, spectral response (SR) measurement has been primarily used to characterize the electrical performance of the sub-cells in multi-junction photovoltaic cells, which is based on the current limiting effect of applying bias lights on other sub-cells [16,17]. Previous studies have manifested that light-emitting diodes and tungsten lamps with filters whose wavelength ranges were mainly in the SR range of other sub-cells can serve as proper bias lights to make the interested sub-cell current-limiting, which has been widely applied in the SR measurement of MJ solar cells [18][19][20][21][22][23]. However, it's not suitable for the SR measurement of GaAs MJLPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, spectral response (SR) measurement has been primarily used to characterize the electrical performance of the sub-cells in multi-junction photovoltaic cells, which is based on the current limiting effect of applying bias lights on other sub-cells [16,17]. Previous studies have manifested that light-emitting diodes and tungsten lamps with filters whose wavelength ranges were mainly in the SR range of other sub-cells can serve as proper bias lights to make the interested sub-cell current-limiting, which has been widely applied in the SR measurement of MJ solar cells [18][19][20][21][22][23]. However, it's not suitable for the SR measurement of GaAs MJLPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Tandem solar cells of III-V semiconductors can achieve the maximum efficiency, which benefits by an efficient utilization of the solar spectrum and lattice match. Especially, the case of Ge-based III-V triple-junction (TJ) solar cells [1][2][3][4][5] have attracted much attention, which has been widely applied in space for energy supply. To confine the misfit dislocation and minimize the strain, the previous study reported 6 that multijunction (MJ) III-V devices use compositionally graded buffers, which have demonstrated solar-to-electrical conversion efficiency of 39.2% (1 sun AM1.5G).…”
Section: │ Introductionmentioning
confidence: 99%
“…Höhn et al [26] proposed four-junction solar cells based on germanium wafer bonding. The presented structure provided high efficiency, due to employing germanium which required an optimized Ge cell with rear-side passivation and a mirror.…”
Section: Introductionmentioning
confidence: 99%